Na+/H+ Exchanger 3 Is Expressed in Two Distinct Types of Ionocyte, and Probably Augments Ammonia Excretion in One of Them, in the Gills of the Climbing Perch Exposed to Seawater - Chen, Xiu L.; Zhang, Biyan; Chng, You R.; Ong, Jasmine L. Y.; Chew, Shit F.; Wong, Wai P.; Lam, Siew H.; Ip, Yuen K. (Frontiers in Physiology, 2017)
The freshwater climbing perch, Anabas testudineus, is an euryhaline teleost and an obligate air-breather with the ability to actively excrete ammonia. Members of the Na+/H+ exchanger (NHE) family help maintain intracellular pH homeostasis and ionic balance through the electroneutral exchange of Na+ and H+. This study aimed to obtain, from the gills of A. testudineus, the full cDNA coding sequence of nhe3, and to determine the effects of exposure to seawater or 100 mmol l-1 of NH4Cl in fresh water on its mRNA and protein expression levels. Efforts were also made to elucidate the type of ionocyte that Nhe3 was associated with in the branchial epithelium of A. testudineus. The transcript level and protein abundance of nhe3/Nhe3 were very low in the gills of freshwater A. testudineus, but they increased significantly in the gills of fish acclimated to seawater. In the gills of fish exposed to seawater, Nhe3 was expressed in two distinct types of seawater-inducible Na+/K+-ATPase (Nka)-immunoreactive ionocytes. In Nkaα1b-immunoreactive ionocytes, Nhe3 had an apical localization. As these ionocytes also expressed apical Rhcg1 and basolateral Rhcg2, which are known to transport ammonia, they probably participated in proton-facilitated ammonia excretion in A. testudineus during seawater acclimation. In Nkaα1c-immunoreactive ionocytes, Nhe3 was atypically expressed in the basolateral membrane, and its physiological function is uncertain. For A. testudineus exposed to NH4Cl in fresh water, the transcript and protein expression levels of nhe3/Nhe3 remained low. In conclusion, the branchial Nhe3 of A. testudineus plays a greater physiological role in passive ammonia transport and acid-base balance during seawater acclimation than in active ammonia excretion during environmental ammonia exposure.